(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
It is known that sonoat, production, transport system and roads in Uzbekistan after the second jaxon war were in a somewhat difficult situation. By the 70s and 80s of the 20th century, there was considerable development in this system. In particular, progress in the railway system and its impact on society were far more effective. This article will tell you about the positive changes in the railway system in these years.